NEW METHOD FOR DISPOSAL OF GRANULATED PHOSPHORIC SLAG FROM HAZARDOUS GASES - Zatkali Ayranbayuly Estemesov; Andrei Vladimirovich Barvinov; Bakytzhan Kudaibergenovich Sarsenbayev; Tulaganov Abdukabil Abdunabievich; Estemesov Marat Zatkalievich; Askar Mirzamuratovich Khaidarov (Academic Scientific Journal of Chemistry, 2020)
New wet method of decontamination of GPS from hazardous gases (PH3, H2S, HF, etc.) and their sources (Са3P2, CaF2 and CaS) is proposed, since dry methods for decontamination turn out to be inviable due to their difficulty and non-efficiency; thus, GPS in construction (and not only) is used without cleaning pursuant to the existing regulatory documents. The wet method of decontamination of GPS from hazardous gases and their sources is developed based on the following comparative methods: First – 2 kg GPS were dried at temperature of about 600°С at the drying furnace within 5 hours; then the air mixture was measured from the special hole for presence of gases. Second – Dried slag after cooling was ground at the vibration mill to the specific surface of 500 m2 /kg with Na2CO3 additive or cement (5 % by weight) and FeO (3 %) and without such activating and neutralizing additives; then the qualitative content of gases was measured at the mill and in slag. Third –2-kg composited sample of GPS was placed in the laboratory vibration mill and was added with water in ratio 1:6 (slag : water by weight). This mixture was ground with Na2CO3 additive or cement (5 % by weight) and FeO (3 %) and without them to the specific surface of 500 m2 /kg; then, the qualitative content of gases was measured at the mill and in slag. It was determined that: - maximum quantity of gas emission from GPS is observed during drying without decontaminating additives; - in presence of decontaminating additives, gas emission from GPS is reduced by one step – due to neutralizing properties of additives; - grinding of dried GPS assists in additional gas emission therefrom – with additive to a lesser extent, without additive – to a greater extent; - in case of GPS grinding in water environment, gas emission is maximally reduced, and with additive – gases are fully neutralized. It follows from what has been said that irrespective of the GPS treatment method, introduced additives are capable to neutralize gases; however, the wet method is more efficient in comparison with the dry one, since: - the wet method does not require drying of GPS; particles are more easily broken to the necessary specific surface with less time; - in the closed space like the vibration mill, in water environment, gases may not volatilize by any reasons and are fully neutralized with additives and activating agents; - products of interaction of gases with neutralizing and activating additives become the activating components of ground GPS. It is shown that during GPS grinding in water environment, the neutralizing and activating additives provide the chemical, physical-chemical and catalytic reactions in the system (totally they are about 20). Studies of the phase composition, hydration degree of ground GPS and strength of consolidated slag stone produced from ecophosphoslag binding agent show the following: - Na2CO3 has higher activating properties than cement-additive; thus, strength and hydration degree of consolidated ecophosphoslag binding agent with Na2CO3 additive are much higher – achieve correspondingly 79.3…83.5 MPa and 21.7…23.3 %, and with cement-additive – only 28.7…37.9 MPa and 16.8…20.4 %; - Higher activating capability of Na2CO3 in comparison with cement-additive is explained by the fact that: - sodium carbonate in the consolidating system creates the increased alkaline medium (рН12); therefore, glassslag is much dissolved; in its turn, assisting in increase in content of hydrate phases in slag stone; - strengthening of slag stone is positively impacted also by ions Na+ included into hydrated calcium silicates – С-S-H and CSH (I), resulting in generation of new expanded coordination centers, like МеО6, assisting in increase and stability of the crystal latitude and hydrate phase, and this is also the positive factor impacting on increase in strength of slag stone. It is defined that FeO does not only neutralizes hazardous gases and their sources, but activates ground GPS. Neutralizing and activating capability of FeO may be related to presence of electron-free orbitals at the 3d-sublevel of Fe2+ (Fe3+), assisting to iron ions as acceptor with neutralizing and activating properties. It may be supposed that such properties shall be common for the compounds, including the elements of transition metals having electron-free orbitals at the 3d-sublevel. It is detected that consolidated ecophosphoslag binding agent contains mainly two types of hydrated calcium silicates – amorphous tobermorite gel (С-S-H) and submicrocrystalline CSH (I).